2020
DOI: 10.1007/s11274-020-02875-6
|View full text |Cite
|
Sign up to set email alerts
|

Genomic and biotechnological insights on stress-linked polyphosphate production induced by chromium(III) in Ochrobactrum anthropi DE2010

Abstract: The resistance of microorganisms to heavy metals in polluted environments is mediated by genetically determined mechanisms. One such mechanism includes the intracellular sequestration of heavy metals in polyphosphate (polyP) inclusions. In Cr(III) contaminated mediums, Ochrobactrum anthropi DE2010 is able to bind and sequester Cr(III) in polyP inclusions. In order to further study the relationship between Cr(III) tolerance and polyP production in O. anthropi DE2010, we carried out whole genomic sequencing, ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 62 publications
0
4
0
Order By: Relevance
“…( Achbergerová and Nahálka, 2011 ). Previous studies have demonstrated the role of bacterial polyphosphates in the accumulation of heavy metals and radionuclides ( Brim et al, 2000 ; Acharya and Apte, 2013 ; Villagrasa et al, 2020 ). Be9 whole genome sequence analysis indicated the presence of genes codifying for enzymes involved in the synthesis (e.g., polyphosphate kinase) and degradation (e.g., exopolyphosphatase) of polyphosphates ( Martínez-Rodríguez et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…( Achbergerová and Nahálka, 2011 ). Previous studies have demonstrated the role of bacterial polyphosphates in the accumulation of heavy metals and radionuclides ( Brim et al, 2000 ; Acharya and Apte, 2013 ; Villagrasa et al, 2020 ). Be9 whole genome sequence analysis indicated the presence of genes codifying for enzymes involved in the synthesis (e.g., polyphosphate kinase) and degradation (e.g., exopolyphosphatase) of polyphosphates ( Martínez-Rodríguez et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Cu 2+ resistance depends on polyP in many microbial species [13]. The increase in the number of polyP inclusions in the cells of Ochrobactrum anthropi directly correlate with the concentration of Cr(III) in culture medium [14]. The Mn-phosphate complex (Mn-Pi) plays a key role in cellular resistance to oxidative stress [15].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, sequestration of metals inside or outside the cell constitutes another major strategy. For this purpose, polyphosphate‐like granules (pPLGs), long‐chain anionic polymers of phosphate, constitute a non‐selective strategy employed by many bacteria (Keasling & Hupf, 1996 ; Villagrasa et al, 2020 ). Formation and hydrolysis of pPLGs are mainly due to the action of polyphosphate kinases (PPKs) and exopolyphosphatases (PPXs), respectively, and their activities can be modulated by metal concentrations in the cytosol, among other factors (Docampo, 2006 ).…”
Section: Introductionmentioning
confidence: 99%